Um olhar sobre a juventude rural do assentamento Rancho Alegre: permanência ou migração? - Oliveira, Carla Michele Geraldo de (2015)
Recently, studies about the youth are occupying a significant space in Brazilian research. Thus, considering the complexity of modern farming and the importance of young people as key subjects in the family farming development process, this paper aims to identify the variables that influence the youth of settlement Rancho Alegre, in the Chorozinho County, Ceará, to either stay in the rural environment or migrate from it. This study presents qualitative traits and the method chosen was the case study method. Regarding the interpretative intention, it was adopted an approach based upon participant observation achieved through individual semi-structured interviews. The research identified that young people showed significant improvements in living conditions after being beneficiaries of a land purchasing policy when we analyze factors such as food security, habitation/housing, purchase of durable goods, social organization and income. The youth stayed in their production units due to life improvement to them or their family members. The results evidence that if the country provides opportunity to a plot of land, satisfying socioeconomic status, good working conditions, adequate payment for the families‟ maintenance and ac cess to a marketplace in which to sell their production, the youth of the settlement Rancho Alegre wouldn‟t opt for leaving the rural environment.